On collusion sustainability with stacked reversion - Escrihuela-Villar, Marc (2015)
We consider a multi-period oligopoly model to analyze cartel sustainability where a subset of collusive firms is exogenously given. We assume that in case of cheating only the cheater is expelled from the cartel and collusion continues without the cheater. We show that, in our model, when firms compete in quantities and the cartel is sufficiently small, a Stackelberg leader cartel can always be sustained if firms are patient enough. Furthermore, in this case collusion is more easily sustained than when firms play grim trigger strategies. The opposite result is obtained in a price-setting supergame with differentiated products.